Lactobacillus plantarum in black soldier fly (Hermetica illucens) meal modulates gut health and immunity of freshwater crayfish (Cherax cainii). Issue 108 (January 2021) - Foysal, Md Javed; Fotedar, Ravi; Siddik, Muhammad A.B.; Chaklader, Md Reaz; Tay, Alfred
Abstract: Probiotic supplements are being used to improve the growth and immune performance of aquaculture species over the last couple of decades. In recent times, black soldier fly (BSF) is considered as one of the promising sources of alternative protein to fishmeal protein in aqua-diets. Since the freshwater crayfish, marron ( Cherax cainii ), a Western Australian's native and iconic freshwater crayfish species, grows fairly slow under commercial farming environment, this study was aimed to investigate the supplemental effect of BSF and BSF with probiotic bacteria Lactobacillus plantarum (BSFLP) on overall health and immune performance of marron after 56 days of feeding under laboratory conditions. The post-trial data revealed insignificant influences of any diets on growth performance, however, both BSF and BSFLP based diets significantly improved some haemolymph parameters and gut health of marron. High throughput sequence data revealed that both BSF and BSFLP diets significantly improved the diversity of microbial communities including some beneficial bacteria for crustaceans in the hindgut of marron. Further analysis showed that both BSF and BSFLP diets upregulated the expression of some genes in the gut tissue and haemocytes associated with the innate immune response of marron at 48 h post injection. The up-regulation of some immune genes in BSFLP diet group was found significantly linked to OTU abundance for Lactobacillus . The findings of this study could be helpful for improving overall health status of marron. Highlights: Lactobacillus plantarum was added into insect Hermatica illucens based protein diet. The probiotic-insect diet significantly increased the microbial diversity in the gut. Insect based diet significantly enhanced the innate immune response and increased post-challenge marron survival. Lactobacillus, Lactovum and Candidatus Bacilloplasma were found positively correlated to the immunity of marron.